Glass-ceramic Foams Made of Very High Coal Fly Ash Weight Ratio by the Direct Microwave Heating Technique - Lucian Paunescu; Sorin Mircea Axinte; Marius Florin Dragoescu; Felicia Cosmulescu (Journal La Multiapp, 2020)
A high mechanical strength glass-ceramic foam was produced by direct microwave heating at 853 ºC of a very high weight ratio of coal fly ash (82%), calcium carbonate (5%) as a foaming agent, sodium carbonate (13%) as a fluxing agent and water addition (10%). Due to the excellent energy efficiency of the direct microwave heating, the heating rate had a very high value (32 ºC/min), much higher than the heating rate of conventional processes and led to a very low value of the specific energy consumption (0.72 kWh/kg). The physical and mechanical characteristics of the optimal glass-ceramic foam sample were: apparent density of 1.44 g/cm3, porosity of 26.2%, thermal conductivity of 0.281 W/m·K, compressive strength of 41.3 MPa and water absorption of 0.5%. Given the features of the glass-ceramic foam (very high compressive strength, acceptable porosity and thermal conductivity, very low water permeability, fireproof, chemical stability, no-toxicity, etc., the application domain of this material type may include road and railway constructions, bridge abutments and retaining walls, foundations, drainages, sports grounds and other types of constructions that require high mechanical stress.